2015
DOI: 10.5455/ijmsph.2015.15062015298
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, attitude, and factors associated with risky health habits and behavior of secondary school students, Almajardah, Saudi Arabia

Abstract: Background: Adolescents make up to 20% of the world's population. However, they have traditionally been neglected as a distict target group and subsumed under the proportion of family, women, and child's welfare and health. Objective: To study the prevalence of and attitude toward selected health-risk behaviors (smoking, alcoholism, substance abuse, and violence) and their possible associated risk factors among secondary school students, Almajardah, KSA. Materials and Methods: A cross-sectional study among mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several studies revealed that the reason behind the risk behaviours among youths in most countries is that they are undergoing a developmental transition in a rapidly changing social, economic, political and emotional climate 9 , 10 , 12 . Therefore, this volatile environment in which the society is to survive can be a breeding ground for the development of a very complex set of health-risk behaviours that may be intertwined with one another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies revealed that the reason behind the risk behaviours among youths in most countries is that they are undergoing a developmental transition in a rapidly changing social, economic, political and emotional climate 9 , 10 , 12 . Therefore, this volatile environment in which the society is to survive can be a breeding ground for the development of a very complex set of health-risk behaviours that may be intertwined with one another.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Al Mojamad 11 reiterates that adolescence is a transitional stage of physical and psychological human development occurring during the period from puberty to legal adulthood and while significant development occurs during the teen years, full maturity is by no means complete. Decision-making and future-oriented thinking are not fully developed and for these various reasons, the teen years can be a stressful and fragile time, making adolescents more susceptible to engaging in risky behaviours and be unable to weigh their risks and benefits 12 .…”
Section: Introductionmentioning
confidence: 99%